"Like a Fish Out of Water": The Experience of African American and Latinx Planning Students. Issue 1 (2nd January 2021) - García, Ivis; Jackson, April; Harwood, Stacy A.; Greenlee, Andrew J.; Lee, C. Aujean; Chrisinger, Benjamin
Abstract: Problem, research strategy, and findings: Many planning practitioners, faculty, and students have worked to address diversity and inclusion. However, only a few studies have examined specifically the ways in which African American and Latinx students perceive and experience instruction related to racial/ethnic diversity and the overall diversity climate as part of their urban planning education. This study, conducted by the Association of Collegiate Schools of Planning (ACSP) Planners of Color Interest Group (POCIG), is based on 451 surveys with urban planning students of all racial/ethnic identities and 14 in-depth interviews with African American and Latinx students. Survey results show that most students report an overall supportive and positive climate for diversity within their programs. Nonetheless, survey data also show differences between African American, Latinx, and White students' experiences of bias and discrimination. Furthermore, interviews revealed that African American and Latinx students continue to face challenges in urban planning programs. Takeaway for practice: The educational training of planners, in general, does not attempt to undo discriminatory practices; instead, these racialized tensions move from the classroom to the workplace. Ultimately, strategies to diversify the planning profession fail because of exclusionary interpersonal and institutional practices. Findings provide insight into how to better support African American and Latinx students in academia and as future practitioners. Results also suggest that greater representation of African American and Latinx students, coupled with mentorship, the creation of counter-spaces, and faculty/staff training on racial microaggressions, could foster more inclusive learning environments in urban planning institutions. Fostering inclusive environments will, in turn, help students learn how to develop healthy relationships with diverse communities. These interpersonal skills likely will translate into a more welcoming workplace and expand opportunities for effectively engaging Latinx and African American communities.